PENGARUH PEMBERIAN BUAH PEPAYA TERHADAP PENYERAPAN TABLET FE PADA IBU HAMIL YANG ANEMIA DI WILAYAH KERJA PUSKESMAS MESKOM - Oktavianti, Erika; Oktora Sri, Ary; Rahmita, Hirza; Lisviarose, Lisviarose (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Anemia is one of the indirect causes of the most bleeding in women giving birth. The prevalence of anemia in pregnancy in Bengkalis Regency is 16.90%. Fe tablets are useful for increasing Hb levels. One way to increase the work of Fe is by consuming papaya fruit which contains vitamin C. The aim of this research is to determine the effect of giving papaya fruit on the absorption of Fe tablets in pregnant women with anemia. Type of experimental research with a two group pretest and posttest design. The research was conducted in December - January 2025 in the Meskom Community Health Center Working Area. Population of 20 anemic pregnant women. This research uses an experimental sample formula with a sample size of 20 people. Accidental Sampling sampling technique. The instruments used were digital Hb and observation sheets. T-Test statistical test data processing. The Dependent T-Test used was the Paired Samples Test. The average Hb level before being given Fe tablets was 9.60 gr/dl, after being given Fe tablets 12.11 gr/dl. The average Hb level before being given Fe tablets and papaya fruit was 10.01 gr/dl, after being given Fe tablets and papaya fruit was 12.76 gr/dl. The effect of giving Fe tablets on increasing Hb levels with p value = 0.000. Effect of giving Fe tablets and papaya with p value = 0.000. The difference in the effectiveness of giving Fe tablets compared to giving Fe tablets and papaya with p value = 0.031. It was concluded that giving Fe tablets and papaya was more effective than giving Fe tablets alone. It is hoped that it can treat or alleviate the problems of pregnant women who experience anemia by giving papaya fruit and Fe tablets.Keywords : Papaya fruit; Fe Tablets; Anemia; Hemoglobin; Pregnant mother